Can Inner Experience Be Apprehended in High Fidelity? Examining Brain Activation and Experience from Multiple Perspectives - Hurlburt, Russell T.; Alderson-Day, Ben; Fernyhough, Charles; Kühn, Simone (Frontiers in Psychology, 2017)
We discuss the historical context for explorations of “pristine inner experience,” attempts to apprehend and describe the inner experiences that directly present themselves in natural environments. There is no generally accepted method for determining whether such apprehensions/descriptions should be considered high fidelity. By analogy from musical recording, we present and discuss one strategy for establishing experiential fidelity: the examining of brain activation associated with a variety of experiential perspectives that had not been specified at the time of data collection. We beeped participants in an fMRI scanner at randomly-determined times and recorded time-locked brain activations. We used Descriptive Experience Sampling (DES) to apprehend and describe the participant’s experience that was ongoing at each beep. These apprehensions/descriptions were obtained with no specific theoretical perspective or experimental intention when originally collected. If these apprehensions/descriptions were of high fidelity, then these pairings of moments of experience and brain activations should be able to be productively examined and re-examined in multiple ways and from multiple theoretical perspectives. We discuss a small set of such re-examinations and conclude that this strategy is worthy of further examination.